Comportamento defensivo de Odontophrynus americanus (Duméril & Bibron, 1841) (Amphibia, Anura, Odontophrynidae) - Maffei, Fábio [UNESP]; Ubaid, Flávio Kulaif (Pensoft Publishers, 2016)
Anurans are a common prey of various animals and some species have developed defense mechanisms against predators. One of these mechanisms is the stiff-legged, in which individuals change their posture to a flat body with stiff and stretched members. Here we report the first record of this behavior in Odontophrynus americanus, a small toad widespread in the southern portion of South America. We believe that this behavior aims to reduce the chances of being seen by the predator.
Defensive behavior of Odontophrynus americanus (Duméril & Bibron, 1841) (Amphibia, Anura, Odontophrynidae)
Keywords: Brazil; Camouflage; Defensive strategy; Frog; Neotropical; Stiff-legged